The Implementation of SAW Method in Applying Employees Leave At The Regional Secretariat Office Of Bengkulu - Zuhri, M. Khoiruddin; Yulianti , Liza; Supardi , Reno (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
The Regional employment Agency of Bengkulu Province is one of the government agencies that has the main role to helping head of regional civil service officer to implement the management of civil servants. Employees who have worked for a certain period of time are given to apply for leave, there are several types of leave such as annual leave, sabbatical leave, sick leave, maternity leave, and leave for important reasons. In line with this, the governance is required to be able to make decisions quickly and carefully, to determine which employees are more important to give the permission, the length of the process selection its make the employee having to wait for leave approval letters. Consequently it’s a problem in the process of granting the leave. Therefore, in this research, will be developed a system that will help the governance determine who is eligible to get the leave by applying the Simple Additive Waighting (SAW) method, with Visual Basic Net programming language, with SQL server database as storage media support, so that the process of determining employee leave can be done using the application.